THE EFFECTIVENESS OF PROVIDING NUTRITION EDUCATION ON IMPROVING FEEDING PRACTICES TO TODDLERS AS AN EFFORT TO PREVENT STUNTING IN SIDOKERTO VILLAGE, PURWOMARTANI KAPANEWON KAPANEWON KASAN DIY - Casnuri; Endang Lestiawati; Nur Hayani (Lppm Unan, 2022)
long term resulting in impaired growth in children and developmental disorders in children caused by malnutrition. Feeding practices are one of the factors that contribute to the incidence of stunting, so nutrition education is needed regarding feeding practices. Research Objectives: To determine the effect of nutrition education interventions on improving knowledge and feeding practice in mothers with toddlers 0-5 years in Sidokerto Hamlet, Purwomartani Kapanewon Kalasan. Research Method: Using a quasi-experimental design with a pre-post test two group design. The number of research subjects in groups one and two were 15 people each. The intervention was in the form of nutrition education using IYCF booklets, a list of household sizes and examples of dishes given 3 times with an interval of 2 weeks. The data collected included mother's age, education, working status, received nutrition counseling, pre-post knowledge, pre-post feeding practice. The statistical analysis used was the Wilcoxon test. The results showed that there was a significant mean difference in the knowledge scores before and after the intervention in the two groups (p=0.006; p=0.003), there was a significant mean difference in the feeding practice scores before and after the intervention in the two groups (p=0.002; p=0.05).